Evaluation of age retardation effect of antioxidants in dense-graded asphalt (DGA) mixture using large molecular size. (15th September 2017) - Jeong, Seung Ho; Xiao, Feipeng; Kim, Yeong Sam; Kim, Kwang W.
Highlights: The age-hardening of asphalt in dense-graded HMA mix was evaluated after short-term aging (SA) and long term aging (LA). The large molecular size (LMS) from GPC was efficiently used for aging level evaluation in a speedy way. The hydrated lime (HL) and a polymer stabilizer (KL) were effective for reducing age hardening of HMA mix. The absolute viscosity was reduced by 33% and 25% after SA and LA, respectively, using KL and HL in HMA mixes. Abstract: This study evaluated the effectiveness of antioxidant (AO) on retarding aging of asphalt mixture using the large molecular size (LMS) of gel-permeation chromatogram (GPC) technique. A polymer stabilizer (designated as KL) and a hydrated lime (HL) were used for preparing dense-graded asphalt (DGA) mixes to examine the effect of the AOs on age retardation. The asphalt mixtures prepared with and without AO were aged artificially in two stages; the short-term aging (SA) for one hour at 160 °C and the long-term aging (LA) for one week at 76 °C. The LMS values were used in the statistical test for estimation of age retardation effect of the AOs and for predicting absolute viscosity. It was found that the KL and HL were effective for inducing reduction of aging significantly at α = 0.05 after SA and LA. Therefore, it was found that the LMS, which was obtained by GPC test, was a dependable variable that can be used for evaluation of age retardation. It was also observed that the KL and HL did apparently have an effect of reducing the AV, predicted by LMS, after SA and LA.